Alas Kaki Penimbang Berat Badan Dengan Berjalan berbasis Sensor Load Cell dan Metode Regresi Linier - Afflatuslloh Adi Salung; Hurriyatul Fitriyah; Dahnial Syauqy (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The ideal body is everyone's dream. From teenagers to old people, both male and female, definitely want the ideal body. The ideal body can be obtained from sufficient exercise, a healthy diet, and adequate sleep. We can find out whether our bodies are ideal or not by measuring their body height and body weight, which are adjusted from the person's age. Monitoring weight is one of the needs to maintain a healthy body. We should always check our weight, so we can control the body's healthy patterns. Sometimes measuring weight takes time, for busy people it may not be important. In fact it is very necessary to always know the weight. It will be very helpful if there is a weight meter that can be used at any time and is not required to stand still on a regular weight scale. Therefore we need a tool that can make it easier for us to monitor our weight at any time. We can check our weight when sleeping, running, eating, and all daily activities. In this study, we will create a wearable device that adds the function of sandals to a weight monitoring tool. By using several Load Cell sensors on the sandal, these sensors function to get the value of the Load Cell sensor which will be processed with the Wemos D1 microcontroller. The results of the process will come out on android devices that are commonly used every day. We can use this tool like an ordinary scale, when standing upright we can get a weight value, and this tool can also be used when walking conditions. In this study, we will focus on examining the device while walking. With this tool, we can make it easier for users to monitor their weight during daily activities without using ordinary scales.